OPTIMIZATION TREATMENT OF UROGENITAL DISORDERS IN MENOPAUSAL WOMEN - E. I. Ermakova; V. E. Balan (IRBIS LLC, 2016)
The relevance of urogenital disorders will steadily increase. In recent years the problem of urination disorders on attention. The most common and difficult in terms of treatment is imperative (urgent) form of incontinence as part of overactive bladder (OAB) syndrom. The article presents the results of clinical trials on the effectiveness of combination therapy (tolterodine and topical forms of estriol) compared with monotherapy of m-cholinergic antagonists (tolterodine) in peri- and postmenopausal women with OAB. The study confirmed that local forms of hormone replacement therapy for peri- and postmenopausal women with OAB increases the efficacy of m-cholinoblokers.